Pengaruh Tata Kelola Perusahaan, Struktur Modal, Struktur Aktiva terhadap Financial Distress dengan Kinerja Keuangan sebagai Variabel Intervening pada sub sektor Rokok yang terdaftar di Bursa Efek Indonesia periode 2016-2023 - Alhabsyi, Amru Karim; Nugroho, Mulyanto (Cattleya Darmaya Fortuna, 2025)
The objective of this research is to examine the impact of Corporate Governance, Capital Structure, and Asset Structure on Financial Distress with Financial Performance as an Intervening Variable. The population of this study includes cigarette sector companies listed on the Indonesia Stock Exchange. The data were obtained from the annual financial reports of 4 cigarette sub-sector companies for the period 2016–2023, using a saturated sampling technique. This study employed is a quantitative approach with data analysis conducted using the Structural Equation Model (SEM) through Partial Least Squares (PLS). The analysis covers the Outer Model, Inner Model, and Hypothesis TestingThe study's findings reveal that Corporate Governance has a positive but insignificant influence on Financial Distress. Similarly, Capital Structure negatively impacts Financial Distress, though the effect is also insignificant, while Asset Structure exerts a positive yet insignificant influence. On the other hand, Corporate Governance demonstrates a positive and significant effect on Financial Performance, whereas Capital Structure and Asset Structure both exhibit negative but insignificant effects. Financial Performance, however, positively and significantly impacts Financial Distress. As an intervening variable, Financial Performance significantly and positively mediates the link between Corporate Governance and Financial Distress, while its mediation of the relationships between Capital Structure and Financial Distress, as well as Asset Structure and Financial Distress, is negative but insignificant.